PEP-1-FK506BP inhibits alkali burn-induced corneal inflammation on the rat model of corneal alkali injury - Kim, Dae Won (BMB Rep, 2015)
FK506 binding protein 12 (FK506BP) is a small peptide with a single FK506BP domain that is involved in suppression of immune response and reactive oxygen species. FK506BP has emerged as a potential drug target for several inflammatory diseases. Here, we examined the protective effects of directly applied cell permeable FK506BP (PEP-1-FK506BP) on corneal alkali burn injury (CAI). In the cornea, there was a significant decrease in the number of cells expressing pro-inflammation, apoptotic, and angiogenic factors such as TNF-α, COX-2, and VEGF. Both corneal opacity and corneal neovascularization (CNV) were significantly decreased in the PEP-1-FK506BP treated group. Our results showed that PEP-1-FK506BP can significantly inhibit alkali burn-induced corneal inflammation in rats, possibly by accelerating corneal wound healing and by reducing the production of angiogenic factors and inflammatory cytokines. These results suggest that PEP-1-FK506BP may be a potential therapeutic agent for CAI. [BMB Reports 2015; 48(11): 618-623]